PENGARUH KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI MAKASSAR - Giovani, Ade Damayanty Vina; Rosyada, Dini (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tadulako, 2019)
This study aims to examine and analyze the influence of competencies and independence on audit quality in Public Accountant Office in Makassar. A questionnaire was distributed to the auditors totaling 50 auditors in seven public accountant offices. The analytical method used is multiple regression analysis. The results of the study show that auditor competency has a positive and significant effect on audit quality. Auditor independence also has a significant effect on audit quality. This results reveal that auditor competency and independency can improve audit quality.